2016
DOI: 10.4025/actascitechnol.v38i2.27440
|View full text |Cite
|
Sign up to set email alerts
|

<b>Photodegradation of sugarcane vinasse: evaluation of the effect of vinasse pre-treatment and the crystalline phase of TiO<sub>2</sub>

Abstract: ABSTRACT. In this work, the effect of vinasse pre-treatment and anatase content in the photocatalytic degradation of sugarcane vinasse was evaluated. The in nature vinasse was pretreated by coagulation/flocculation using vegetal tannin as coagulant and diluted 1: 2 with deionized water. The photocatalytic tests with in nature, pretreated and diluted vinasse were performed for 48 hours under UV radiation using 1 g of catalyst: TiO 2 Kronos calcined at 300 o C (100% anatase) and 1000 o C (34% anatase) and TiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The TNT synthesized in this study also possessed relatively low pore size and pore volume. This observation can be related to the presence of a high number of functional groups at the pore entrance, as based on a previous study [ 32 ]. The pore volume with small average pore size indicates more pores with smaller size were distributed along the tubular structure.…”
Section: Resultssupporting
confidence: 60%
“…The TNT synthesized in this study also possessed relatively low pore size and pore volume. This observation can be related to the presence of a high number of functional groups at the pore entrance, as based on a previous study [ 32 ]. The pore volume with small average pore size indicates more pores with smaller size were distributed along the tubular structure.…”
Section: Resultssupporting
confidence: 60%
“…A large number of studies have shown that red is easy to recognize by the human eye. erefore, based on this fact, the image of the image target can be mapped to the red channel first, so that the background can be easily recognized [11][12][13]. Since human eyes have different perceptions of the color brightness of monochromatic light, in the image spectrum of the three primary colors, it is easy to think that green is the brightest.…”
Section: Pfa Algorithmmentioning
confidence: 99%
“…In view of the widespread contamination of the environment by persistent and toxic chemical pollutants from industrial wastewater, it is essential to develop economical methods for their remediation. One of the major problems of the sugar and alcohol industries is the large volume of waste generated, mainly vinasse, which represents a potential pollutant when inadequately administered (Ferreira et al, 2010;Colin et al, 2016;Souza et al, 2016;Hoarau et al, 2018). Sugarcane vinasse is an effluent that can present variation in its composition, depending on the raw material used and the process used in the distillation of ethanol.…”
Section: Introductionmentioning
confidence: 99%